THU0275 IL-6 Receptor (IL-6R) Blockade with Sarilumab Reduced Circulating Markers Related to Synovial Inflammation and Structural Damage in Patients with Rheumatoid Arthritis (RA) in A Phase 2 Study. (10th June 2014) - Fiore, S.; Boyapati, A.; Hamon, S.C.; van Adelsberg, J.; Liu, M.; Hamilton, J.D.
Abstract : Background: Sarilumab is the first fully-human monoclonal antibody directed against the IL-6R and is being investigated for the treatment of RA. Patients with RA have elevated tissue turnover at sites of inflammation, resulting from increased activity of proteases, including matrix metalloproteinase (MMP). MMP-cleaved fragments of collagen type 1 (C1M), collagen type 2 (C2M), collagen type 3 (C3M), and C-reactive protein (CRPM) are elevated in sera from patients with RA and reductions may be associated with treatment response. Indeed, the C1M neo-epitope has been recently identified as a potentially prognostic biomarker of bone erosion. Objectives: The objective of this study was to determine whether sarilumab reduces the levels of serum biomarkers related to synovial inflammation and joint damage in patients with RA. Methods: MOBILITY part A was the dose-ranging phase 2 portion of the MOBILITY trial of subcutaneous sarilumab in patients with active RA treated with concomitant methotrexate (MTX). Sera were collected at baseline, 2 weeks, and 12 weeks from patients randomized to treatment with MTX+placebo (Pbo), MTX+sarilumab 150 mg q2w, or MTX+sarilumab 200 mg q2w. C1M, C2M, C3M and CRPM were analyzed by ELISA. Results: Baseline levels of each biomarker were similar among treatment groups. Sarilumab treatment at both doses resulted in marked reduction in levels of C1M, C2M, C3M and CRPM from baseline at 2 weeks (Table, percent change from baseline ± SE) and suppression of each marker was maintained at 12 weeks (data not shown). In contrast, in the MTX+Pbo group there was no significant decrease in these biomarkers at both 2 and 12 weeks. Observed AEs were similar to those reported with other IL-6 inhibitors. Conclusions: Sarilumab treatment in patients with RA resulted in significant dose-dependent reduction in MMP-generated neo-epitope biomarkers related to joint and tissue turnover. The most dramatic reduction associated with sarilumab treatment was observed with the C1M neo-epitope, a potentially prognostic biomarker of structural damage (ref). Additional studies are needed to determine if reduction of MMP-cleaved fragments, such as C1M or CRPM, predict clinical and/or radiographic responses (bone erosion and/or joint space narrowing) in patients treated with sarilumab. References: AS Siebuhr et al. Serological identification of fast progressors of structural damage with rheumatoid arthritis. Arthritis Research & Therapy 2013, 15:R86 doi:10.1186/ar4266. Acknowledgements: Sponsored by Sanofi and Regeneron Pharmaceuticals Inc. (NCT01061736 ). Disclosure of Interest: : S. Fiore Shareholder of: Sanofi US, Employee of: Sanofi US, A. Boyapati Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., S. Hamon Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., J. van Adelsberg Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., M. Liu Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., J. Hamilton Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc. DOI: 10.1136/annrheumdis-2014-eular.3852